Konseling Pastoral terhadap Orang Tua Kristen yang Mengalami Kelelahan Emosional dalam Mengasuh Anak (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
Christian parents frequently negotiate intensive caregiving expectations, moral responsibility, economic pressure, and ecclesial ideals of faithful family life. These demands may produce emotional exhaustion that resembles parental burnout but is often interpreted only as spiritual weakness or lack of discipline. This constructive study aims to formulate a restorative-integrative model of pastoral counseling for Christian parents who experience emotional exhaustion in childrearing. The method is a qualitative literature study using integrative narrative synthesis of peer-reviewed studies on parental burnout, religious coping, family support, and Christian pastoral counseling. The analysis identifies four central findings: emotional exhaustion is the core symptom that drives distancing and reduced parental efficacy; burnout emerges from an imbalance between risks and resources; spiritual narratives can function either as resources or as sources of guilt; and pastoral counseling is most constructive when it combines empathic presence, theological reframing, emotion regulation, communal support, and referral ethics. The study implies that churches need pastoral systems that normalize help-seeking, protect parents from moralistic judgment, and connect spiritual care with psychologically informed intervention.